When will the COVID-19 Pandemic in Indonesia End? - Susanna, Dewi (Kesmas, 2020)
On January 30, 2020, the World Health Organization(WHO) declared 2019-nCOV to be a Public Health Emergency of International Concern (PHEIC), due to the significant increase in confirmed new cases in various countries.1 In Indonesia, the first confirmed COVID-19 case was a female who had a closed contact with the 24th confirmed case in Malaysia and the second case was the mother of the first case.2 As time goes by, the number of new cases has increased significantly, reaching 160.165 confirmed cases with 6,944 deaths by August 27, 2020.3 The time when the COVID-19 pandemic in Indonesia will end is not known, although some studies are attempting to predict this such as in articles, journals, newspapers, and other media.